Origin and history of ureilitic material in the solar system: The view from asteroid 2008 TC3 and the Almahata Sitta meteorite. (18th December 2014) - Goodrich, Cyrena Anne; Hartmann, William K.; O'Brien, David P.; Weidenschilling, Stuart J.; Wilson, Lionel; Michel, Patrick; Jutzi, Martin
Abstract Asteroid 2008 TC3 (approximately 4 m diameter) was tracked and studied in space for approximately 19 h before it impacted Earth's atmosphere, shattering at 44–36 km altitude. The recovered samples (>680 individual rocks) comprise the meteorite Almahata Sitta (AhS). Approximately 50–70% of these are ureilites (ultramafic achondrites). The rest are chondrites, mainly enstatite, ordinary, and Rumuruti types. The goal of this work is to understand how fragments of so many different types of parent bodies became mixed in the same asteroid. Almahata Sitta has been classified as a polymict ureilite with an anomalously high component of foreign clasts. However, we calculate that the mass of fallen material was ≤0.1% of the pre‐atmospheric mass of the asteroid. Based on published data for the reflectance spectrum of the asteroid and laboratory spectra of the samples, we infer that the lost material was mostly ureilitic. Therefore, 2008 TC3 probably contained only a few percent nonureilitic materials, similar to other polymict ureilites except less well consolidated. From available data for the AhS meteorite fragments, we conclude that 2008 TC3 samples essentially the same range of types of ureilitic and nonureilitic materials as other polymict ureilites. We therefore suggest that the immediate parent of 2008 TC3 was the immediate parent of all ureilitic material sampled on Earth. We trace critical stages in the evolution of that material through solar system history. Based on various types of new modeling and re‐evaluation of published data, we propose the following scenario. (1) The ureilite parent body (UPB) accreted 0.5–0.6 Ma after formation of calcium‐aluminum‐rich inclusions (CAI), beyond the ice line (outer asteroid belt). Differentiation began approximately 1 Ma after CAI. (2) The UPB was catastrophically disrupted by a major impact approximately 5 Ma after CAI, with selective subsets of the fragments reassembling into daughter bodies. (3) Either the UPB (before breakup), or one of its daughters (after breakup), migrated to the inner belt due to scattering by massive embryos. (4) One daughter (after forming in or migrating to the inner belt) became the parent of 2008 TC3. It developed a regolith, mostly ≥3.8 Ga ago. Clasts of enstatite, ordinary, and Rumuruti‐type chondrites were implanted by low‐velocity collisions. (5) Recently, the daughter was disrupted. Fragments were injected or drifted into Earth‐crossing orbits. 2008 TC3 comes from outer layers of regolith, other polymict ureilites from deeper regolith, and main group ureilites from the interior of this body. In contrast to other models that have been proposed, this model invokes a stochastic history to explain the unique diversity of foreign materials in 2008 TC3 and other polymict ureilites.